The Influence of Viral Marketing and Product Quality on Purchase Decision on Contemporary Foods, Sang Pisang - Hendy Tannady; Meilisa Alvita (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to find out the effect of Viral Marketing on Purchase Decisions for the current food Sang Pisang in Cempaka mas. The second is to determine the effect of product quality on purchasing decisions for Sang Pisang contemporary food in Cempaka Mas. The third is to find out the effect of Viral Marketing and Product Quality on Purchase Decisions for the current Sang Pisang food in Cempaka Mas. This research uses a quantitative approach. The data collection used by researchers is through a questionnaire. The population in this research are people who know Sang Pisang products. Determination of the sample used is a non-probability sampling technique with purposive sampling method. The sample used was 162 respondents with the criteria of respondents coming from consumers who had bought Sang Pisang products. Based on the research that has been done, the researcher can conclude that the Viral Marketing Variable separately (partially) influences purchasing decisions. Product quality variables separately (partially) influence purchasing decisions. Viral marketing variables (X1) and product quality (X2) simultaneously influence purchasing decisions (Y)